Market structure, welfare, and banking reform in China - Chun-Yu Ho (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
This paper examines the effects of market deregulation on consumers and state commercial banks in China, a large developing country. I jointly estimate a system of differentiated product demand and pricing equations under alternative market structures. While China's banking reforms overall have achieved mixed results, the consumer surplus of the deposit market has increased. The welfare effects from reforms are unevenly distributed, with losses skewed toward inland provinces and certain consumer groups. There is no clear evidence that the pricing of banking services has become more competitive after the reform, and such pricing remains subject to government intervention. Encouragingly, the price-cost margins of some state commercial banks have fallen over time.
URN:NBN:fi:bof-201408072113
Keywords: 330